Effect of Terramycin® and Bovatec® in free-choice mineral mixtures on gains of heifers grazing native grass - Brazle, F.; Kuhl, Gerry L.; Harmon, D.; Laudert, S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplementing heifers in an intensive-early grazing program with Terramycin ® or Bovatec ® in free-choice, mineral-soybean meal mixtures resulted in Comparable cattle performance. Both feed additive mixtures increased heifer gains about .3 lb per day compared to controls supplemented with a simple mineral mixture.
Keywords: Beef; Terramycin®; Bovatec®; Heifers; Mineral; Native grass